Functional genomics of seed dormancy in wheat: advances and prospects - Gao, Feng; Ayele, Belay T. (Frontiers in Plant Science, 2014)
Seed dormancy is a mechanism underlying the inability of viable seeds to germinate under optimal environmental conditions. To achieve rapid and uniform germination, wheat and other cereal crops have been selected against dormancy. As a result, most of the modern commercial cultivars have low level of seed dormancy and are susceptible to preharvest sprouting when wet and moist conditions occur prior to harvest. As it causes substantial loss in grain yield and quality, preharvest sprouting is an ever-present major constraint to the production of wheat. The significance of the problem emphasizes the need to incorporate an intermediate level of dormancy into elite wheat cultivars, and this requires detailed dissection of the mechanisms underlying the regulation of seed dormancy and preharvest sprouting. Seed dormancy research in wheat often involves after-ripening, a period of dry storage during which seeds lose dormancy, or comparative analysis of seeds derived from dormant and non-dormant cultivars. The increasing development in wheat genomic resources along with the application of transcriptomics, proteomics and metabolomics approaches in studying wheat seed dormancy have extended our knowledge of the underlying mechanisms acting at transcriptional and post-transcriptional levels. Recent progresses indicate that some of the molecular mechanisms are associated with hormonal pathways, epigenetic regulations, targeted oxidative modifications of seed mRNAs and proteins, redox regulation of seed protein thiols and modulation of translational activities. Given that preharvest sprouting is closely associated with seed dormancy, these findings will significantly contribute to the designing of efficient strategies for breeding preharvest sprouting tolerant wheat.